Reductions in Retrobulbar and Retinal Capillary Blood Flow Strongly Correlate With Changes in Optic Nerve Head and Retinal Morphology Over 4 Years in Open-angle Glaucoma Patients of African Descent Compared With Patients of European Descent. Issue 9 (September 2016) - Siesky, Brent; Harris, Alon; Carr, Joseph; Verticchio Vercellin, Alice; Hussain, Rehan M.; Parekh Hembree, Priyanka; Wentz, Scott; Isaacs, Michael; Eckert, George; Moore, Nicholas A.
Abstract : Purpose: To investigate the relationship of changes in ocular blood flow with optic nerve head (ONH) and retinal morphology in open-angle glaucoma (OAG) patients of African versus European descent (ED) over 4 years. Materials and Methods: In this study, 112 patients with OAG were examined at baseline, 79 [59 ED, 20 African descent (AD)] of which were followed for 4 years. Retinal capillary blood flow was assessed with Heidelberg retinal flowmetry. Retrobulbar blood flow was measured by color Doppler imaging. Retinal structural changes were examined with optical coherence tomography and Heidelberg retinal tomography-III. Mixed-model analysis of covariance was used to test for the significance of change from baseline to 4-year follow-up, and Pearson correlation coefficients were calculated to evaluate linear associations. Results: In OAG patients of AD, structural changes of the ONH demonstrated a strong association with the end diastolic velocities and resistive indices of the short posterior ciliary arteries over 4 years. In addition, there was a significantly larger increase in the avascular area of the inferior retina in patients of AD, and this reduction in retinal capillaries strongly correlated with a reduction in macular thickness. Conclusions: Reductions in retinal capillary and retrobulbar blood flow strongly correlated with changes in the ONH and macular thickness over 4 years in OAG patients of AD compared with ED. These data suggest that ocular vascular health may be a more influential contributing factor in the pathophysiology of OAG in patients of AD compared with ED.